Posse e usos da cultura escrita e difusão da escola: de Portugal ao Ultramar, Vila e Termo de São João Del Rei, Minas Gerais (1750-1850) - Christianni Cardoso Morais (2009)
This thesis intends to analyze the ownership, the uses and the dissemination of the culture of the written word, as well as the establishment of schools between the years 1750 to 1850, in Portugal and in Brazil, especially in the town and administrative area of São João del-Rei. This particularly long period, from Colony to Empire, is necessary to perceive the rupture or durability of trends in the various themes developed within the thesis. The geographic boundaries include Minas Gerais (without losing sight of its place in Portuguese America) and the Kingdom of Portugal and Colonies, specifically analyzing the town and administrative area of São João del-Rei, one of the mining localities more populous and urbanized of the period. To attain the proposed objectives, the research involved the use of distinct types of documents, among which were various legislation on education for the whole of the period, school data, reports of diverse organs responsible for the inspection of official schools, manuals of calligraphy, nineteenth century periodicals, documents produced by the town council of São João del-Rei, wills and associated inventories. The analysis of these sources required a combination of quantitative and qualitative methods. If the schools, initiated in 1759 by Dom José I and his powerful minister Carvalho e Melo, were aimed at a small proportion of the royal subjects, if only because school education in the colonial period had in view the maintenance of state order, then the schools financed by the Brazilian Empire were no less exclusive. However, in the first decades of the imperial period there was an attempt to civilize the nation, establishing a sense of patriotism. Elementary schools aimed at the lower levels of the population, were considered an institution capable of producing civilized citizens, at least literate, that could understand the laws and submit to public order. Both colonial and imperial society were, in their own ways, hierarchical and exclusive, but there was, outside public education, a multiplicity of possibilities for those who wished to improve their powers of reading, writing and arithmetic. In this way, the thesis articulates the structure of public education with other alternatives created outside of the public teaching spaces: seminars, the houses of education for orphaned children administrated by religious or lay groups, and even the strategy of some families to contract private tutors, alternatives which were common throughout the period. Through the analysis of all these possibilities of access to the culture of the written word, the thesis allows the demonstration that the Portuguese-Brazilian world, despite having a restricted number of official schools, did not represent a population far removed from the world of letters. There were, indeed, people capable of reading and writing. The written word, manuscript or print, was in circulation and disseminated, and even those unable to read and write were identified as being capable of everyday use of the culture of the written word in diverse and inventive ways.